Effects of gender, cytokine gene polymorphisms and environmental factors on inflammatory responses. Issue 5 (July 2015) - Moscovis, Sophia M; Cox, Amanda; Hall, Sharron T; Burns, Christine J; Scott, Rodney J; Blackwell, C Caroline
Previous studies have indicated that cytokine gene polymorphisms of Indigenous Australians were predominantly associated with strong pro-inflammatory responses. We tested the hypothesis that cells of donors with genetic profiles of inflammatory cytokine single nucleotide polymorphisms (SNPs) similar to Indigenous Australians produce higher pro-inflammatory responses. PBMCs from 14 donors with genetic profiles for a high risk of strong pro-inflammatory responses and 14 with low-risk profiles were stimulated with endotoxin and effects of gender, IFN-γ, cigarette smoke extract (CSE) and testosterone on cytokine responses analysed. Cytokines were calculated from standard curves (Luminex 2.3 software). No significant differences were associated with SNP profile alone. Lower pro-inflammatory responses were observed for cells from males with low- or high-risk profiles. For cells from females with high-risk profiles, anti-inflammatory IL-10 responses were significantly reduced. There was no effect of testosterone levels on responses from males. For females, results from IFN-γ-treated cells showed positive correlations between testosterone levels and IL-1β responses to endotoxin for both risk groups and TNF-α for the high-risk group. If interactions observed among CSE, IFN-γ, genetic background and testosterone reflect those in vivo, these might contribute to increased incidences of hospitalisations for infectious diseases among Indigenous women.